Pola Asuh Permisif Orang Tua Terhadap Sikap Bullying Yang Dilakukan Siswa Di Sekolah: Analisis Literatur - Sofia, Maria Luciana (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2025)
This study aims to analyze the relationship between permissive parenting styles and bullying attitudes among students at school through a systematic literature review. The method used is a literature review with a qualitative approach to various national and international journal sources. The results of the analysis show that permissive parenting, characterized by unlimited freedom, minimal guidance, and low parental control, contributes significantly to the formation of bullying attitudes. This relationship occurs through three main channels: (1) failure to develop emotional regulation and self-control, which triggers impulsive and aggressive behavior; (2) impeded development of empathy, which causes indifference to the suffering of victims; and (3) ignorance of social norms and behavioral consequences, which creates the perception that aggressive actions can be carried out without serious repercussions. The implications of this study emphasize the importance of a collaborative approach between parents and schools through the implementation of balanced parenting, continuous parenting education programs, and the strengthening of social-emotional skills curricula to break the chain of bullying and create an environment that supports optimal child development.